MENINGKATKAN KONTROL PENGGUNA DAN MEKANISME PERSETUJUAN UNTUK PERLINDUNGAN PRIVASI DATA PRIBADI. - Neha Chintya; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
. In an increasingly advanced digital era, the use of information technology has become an integral part of our daily lives. The presence of information technology has made it easier to access and use personal data. However, with this progress, there are also growing concerns regarding the privacy of users' personal data. This journal discusses strategies to improve user control and consent mechanisms to effectively protect the privacy of personal data. The approach used includes the use of encryption technology, appropriate access settings, and transparency in data use. This journal also covers the importance of compliance with applicable privacy regulations and the active role of users in understanding and managing access permissions to personal data. By implementing this strategy, it is hoped that it can create a safer and more trustworthy digital environment for users to maintain the privacy of their personal data and this research also aims to present solutions that are effective and can be applied in the modern digital environment.